MAKNA TANAH PENGUNGSIAN BAGI JEMAAT GPM BANDA SULI - Winde Dale Tuhumena; John Chr Ruhulessin; M M Hendriks (Program Pascasarjana UKIM, 2020)
The congregation of Banda Suli (Read: Jemaat GPM Banda Suli) is one of the members of the Protestant Church in the Moluccas (GPM). The members of Jemaat GPM Banda Suli have initially displaced members of the congregations in the Banda Islands due to the 1999 conflict. Accustomed to living with extensive land ownership with Banda identity as Banda people, then settling in small, limited land with identity as a Banda people in the land of Suli need the right meaning to be able to improve the welfare of life. This research uses qualitative methods with in-depth interview techniques and literature studies. The results of the study found that by experiencing God's presence in the land they inhabited, both on the island of Banda and in the land of Suli, they had the spirit and were motivated to continue working and trying to improve the existence of their lives. The land of Suli Banda is also understood as the Holy ground for God.